1)
Проверка: 1+1=2 - верно.
ответ: 5
2)
ответ: 3
Мы воспользовались формулой
Ее можно доказать, прологарифмировав левую и правую части по основанию b.
1)![\log_5x+\log_x5=2;\ x0;\ x\not= 1;\ \log_5x+\dfrac{1}{\log_5x}=2;\ \log_5x=t;](/tpl/images/4554/0782/900ea.png)
Проверка: 1+1=2 - верно.
ответ: 5
2)![x^{\log_36}+6^{\log_3x}=12;\ 6^{\log_3x}+6^{\log_3x}=12;\ 6^{\log_3x}=6^1;\ \log_3x=1; x=3.](/tpl/images/4554/0782/72d34.png)
ответ: 3
Мы воспользовались формулой![a^{\log_bc}=c^{\log_ba}\ \ (a0; b0; c0; b\not=1).](/tpl/images/4554/0782/5479e.png)
Ее можно доказать, прологарифмировав левую и правую части по основанию b.